Pengaruh Brand Global dan Kualitas Produk terhadap Loyalitas Konsumen dengan Kepuasan Konsumen sebagai Variabel Intervening: Studi pada Merek Indomie di Kalangan Mahasiswa Universitas Palangkaraya - Bunga Noor Aziza; Krisna Krisna; Milliana Milliana; Okta Kurnia; Oktavia Riani; Rahmadi Rahmadi; Srimelda Oktavia (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
Global brand competition and the importance of product quality are key factors in shaping consumer loyalty, especially among students as young consumers. This study aims to analyze the influence of global brands and product quality on consumer loyalty with consumer satisfaction as an intervening variable. The object of the research is a student of the University of Palangka Raya as a consumer of the Indomie brand. The approach used is quantitative with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, based on data from 75 respondents selected through purposive sampling techniques. The results of the study show that product quality has a positive and significant effect on consumer satisfaction and loyalty. Consumer satisfaction has also been shown to have a significant effect on loyalty and mediates the relationship between product quality and consumer loyalty. In contrast, global brands do not have a significant influence on consumer satisfaction or loyalty. These findings emphasize that product quality has a more dominant role than global brand image in shaping consumer loyalty to Indomie.